Transformation of Al-Qur'an Memorization Learning in the Digital Age through the Blended Learning Flipped Classroom Approach - Zakariyah Zakariyah; Abdul Muhid; Miftah Arifin (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
The rapid advancement of digital technology has significantly transformed educational paradigms, including Qur’an memorization, which traditionally relied on oral, repetitive methods. This study explores the integration of the blended-learning, flipped-classroom model as an innovative approach to enhance Qur’an memorization in the digital era. The purpose of this research is to examine how the model influences students’ motivation, engagement, and memorization effectiveness while maintaining the spiritual and pedagogical values of Islamic education. Employing a qualitative case study design, data were collected through in-depth interviews, surveys, classroom observations, and document analysis involving 120 students, 10 teachers, and the school leadership of SMP Al-Furqon Kota Baru Driyorejo. The findings reveal that students’ motivation scores increased from 2.8 to 4.1 on a five-point Likert scale, and the average memorization rate improved from 5.3 to 8.7 verses per week after the model’s implementation. Additionally, students demonstrated greater self-regulation and active participation, while teachers reported more efficient classroom interaction and feedback. Despite challenges such as limited digital literacy and infrastructure, these were mitigated through targeted training and institutional support. The study implies that integrating digital pedagogy within Qur’an memorization not only enhances cognitive and motivational outcomes but also offers a transformative framework for modern Islamic education, aligning traditional spirituality with technological advancement.